2012
DOI: 10.1002/ar.22491
|View full text |Cite
|
Sign up to set email alerts
|

Tooth‐On‐Tooth Interlocking Occlusion Suggests Macrophagy in the Mesozoic Marine Crocodylomorph Dakosaurus

Abstract: Metriorhynchidae was a peculiar but long-lived group of marine Mesozoic crocodylomorphs adapted to a pelagic lifestyle. Recent discoveries show that metriorhynchids evolved a wide range of craniodental morphotypes and inferred feeding strategies. One genus, Dakosaurus, is arguably the most aberrant marine crocodylomorph due to its large, robust, ziphodont teeth; very low tooth count; and brevirostrine/oreinirostral snout. We here report an additional unusual feature of Dakosaurus that is unique among marine cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(86 citation statements)
references
References 49 publications
2
84
0
Order By: Relevance
“…Sediment was initially affixed to the broken surfaces, which were exposed carefully during preparation to identify areas with possible bite damage. The presumed bite damage on the vertebral centra suggests that the fish was broken apart by the mosasaur before being swallowed, a necessary mode of macrophagic feeding in aquatic amniotes to prevent asphyxiation (e.g., Young et al, 2012), with the notable exception of sea snakes and sea kraits (e.g., Greene, 1997).…”
Section: Macrophagy In Mosasaurus Missouriensismentioning
confidence: 98%
“…Sediment was initially affixed to the broken surfaces, which were exposed carefully during preparation to identify areas with possible bite damage. The presumed bite damage on the vertebral centra suggests that the fish was broken apart by the mosasaur before being swallowed, a necessary mode of macrophagic feeding in aquatic amniotes to prevent asphyxiation (e.g., Young et al, 2012), with the notable exception of sea snakes and sea kraits (e.g., Greene, 1997).…”
Section: Macrophagy In Mosasaurus Missouriensismentioning
confidence: 98%
“…Wear striations on fossil teeth demonstrate that dental occlusion evolved independently in ten or more clades of amniote vertebrates, many of them are herbivores like the sail-backed synapsids of the Edaphosauridae [92][93][94][95][96]. Even conodonts, tiny jawless lamprey-like animals that were common in Paleozoic seas, have sophisticated tooth-on-tooth feeding movements [97,98].…”
Section: Occlusion In Non-mammalsmentioning
confidence: 99%
“…5) suggest that it could have been an effective predator of large prey (relative to its body size), including soft-bodied animals. Tightly interlocking teeth have been suggested as an indicator of macrophagy in crocodylians (Young et al 2012), and the anterior and posterior flanges would have formed an almost continuous slicing or cutting surface. The teeth of E. rugosus also have longitudinal ridges (Blais et al 2015), which, in other taxa, have been suggested to indicate the presence of plicidentine (Meunier et al 2014).…”
Section: Discussion Trophic Niche Differentiationmentioning
confidence: 99%